(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2014)
Introduction: Human immunodefi ciency virus infection damages the immune system making those affected more susceptible to opportunistic infections and malignancies which are common in the chest. This study sought to determine the pattern of chest X-ray lesions and the corresponding CD4 counts of HIV positive patients reporting in the antiretroviral clinic of this teaching hospital for the fi rst time. Methodology: Consecutive HIV positive patients that attended the antiretroviral clinic of the Lagos State University Teaching Hospital, (LASUTH) from September 2009 to January 2011 were recruited. Their chest x-rays were assessed for the presence of pulmonary lesions and baseline CD 4 counts were done to assess their degree of immunosuppression. Data were analyzed using the Statistical Package for Social Sciences, version 16.0. Results: There were 211 subjects, 151 females and 60 males with a M:F ratio of 1:2.5 The mean age of participants was 36.5±11.9. Mean baseline CD4 count for the subjects was 279±220.7 cells/mm3. Almost two thirds (64.9%) cases had normal chest x-rays with their mean CD4 count as 277.65±228.54 cells/mm3. The commonest lesions seen in the lungs include pulmonary infi ltrations, 55 (26.1%), cardiomegaly, 24 (11.4%), pulmonary consolidation, 21 (10%) and lymphadenopathy, 14 (6.6%). The commonest radiological diagnosis made were Atypical pneumonitis, 39 (18.5%), pulmonary TB, 13 (6.2%), pneumonia 13 (6.2%) and cardiomegaly13 (6.2%) respectively.Patients with chest findings had lower mean CD4 counts, 239 cells/mm3 when compared to those without, 244 cells/mm3. Conclusion: Pulmonary infiltration was the commonest lesion, while the commonest diagnosis was atypical pneumonitis. Patients with chest x-ray lesions were found to have lower CD4 counts with probable worse destruction of their immune system. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2013; X(2); 27-34 DOI: http://dx.doi.org/10.3126/saarctb.v10i2.9710